The Influence of Environmental Conditions and Vineyard Management Practices on the Composition and Content of Carotenoids in Grapevines (Vitis vinifera L.). A Review - Anić, M.; Karoglan, M.; Osrečak, M.; Karoglan-Kontić, J. (South African Journal of Enology and Viticulture, 2024)
Carotenoids are plant pigments that are important for photosynthesis and photo-protection. In recent years there has been great interest in the role of carotenoids in grapevines. The reason for this interest is that carotenoids are substrates for the synthesis of C13-norisoprenoids, which have a major influence on wine aroma. To optimise the concentration of C13-norisoprenoids in grapes and wine, the environmental conditions and vineyard management practices that may affect carotenoid metabolism in grapes need to be better understood. This paper reviews recent studies on vineyard management practices in terms of carotenoid accumulation, discusses grapevine plasticity, and provides new perspectives for understanding grapevine physiology in response to environmental conditions that affect carotenoid synthesis.